The Role Of Assets In Driving Recurring Revenue In Property And Real Estate - Meliana Kristin Ongkowijoyo; Cliff Kohardinata (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research focuses on empirically testing the influence of fixed assets, cash and leverage have on recurring revenue in the property and real estate sector. The secondary data used comes from the company’s annual financial statements by analyzing quantitatively in this study. The method applied in this study is purposive sampling so that the sample that was successfully collected was 24 property and real estate companies which included the main listing board on the IDX from 2019 to 2022. The data was analyzed by means of multiple linear regression with the help of Stata 13 software. The results of empirical analysis in this research indicate that the fixed assets variable has a positive effect on recurring revenue, cash has a negative effect on recurring revenue. On the other hand, leverage has no effect on recurring revenue. The implications of this study suggest that property and real estate companies should increase fixed assets with strategic plans and low cash forces companies to use strategies that increase recurring revenue growth. Moreover, it is possible that low cash allows increasing fixed assets aimed at increasing recurring revenue.